Esoteric Theravada the story of the forgotten meditation tradition of Southeast Asia - Crosby, Kate 19XX- (Shambhala Publications, Inc., 2020)
"Discover the esoteric branch of Theravada meditation in the first English-language exploration of a practice tradition nearly lost to history. In this groundbreaking book, scholar Kate Crosby illuminates the once-dominant traditional Theravada meditation system known as borān kamahāna. Theravadan Buddhism, though often understood as the school that most carefully preserved the practices originally taught by the Buddha, has in fact undergone tremendous change over time. Prior to Western concerns with the separation of science and religion that influenced Asian Buddhist modernizers, there existed a tradition of embodied, esoteric, and culturally regional Theravadan meditation practices. These meditation systems differ radically from the reformed, text-based meditations that are now taught in Theravada Buddhism, including Vipassana and Insight Meditation, as well as Buddhist and secular mindfulness. Drawing on a quarter century of research, Crosby offers the first holistic discussion of borān kamahāna in the context of historical events and cultural processes by which the practice has been marginalized in the modern era. Readers of Esoteric Theravada will never see Theravada Buddhism in the same light again"--
Keywords: Geschichte; Meditation; Therawada; Südostasien; Borān kammaṭṭhāna (Buddhism); Theravāda Buddhism / Southeast Asia / History; RELIGION / Buddhism / General; Theravāda Buddhism; Southeast Asia; History